Econazole-releasing porous space maintainers for fungal periprosthetic joint infection - Tatara, Alexander M. (J Mater Sci Mater Med, 2018)
While antibiotic-eluting polymethylmethacrylate space maintainers have shown efficacy in the treatment of bacterial periprosthetic joint infection and osteomyelitis, antifungal-eluting space maintainers are associated with greater limitations for treatment of fungal musculoskeletal infections including limited elution concentration and duration. In this study, we have designed a porous econazole-eluting space maintainer capable of greater inhibition of fungal growth than traditional solid space maintainers. The eluted econazole demonstrated bioactivity in a concentration-dependent manner against the most common species responsible for fungal periprosthetic joint infection as well as staphylococci. Lastly, these porous space maintainers retain compressive mechanical properties appropriate to maintain space before definitive repair of the joint or bony defect.